A Systematic Review of Psychological Well-being in Working Mothers with Children with Special Needs - Dwika Rachma Widyantini; Iriani Indri Hapsari; Lussy Dwiutami Wahyuni; Zarina Akbar (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
The role of women in the family is no longer limited to being the primary caregiver, but also as important contributors to the economy. This has led to many women having to juggle dual roles as mothers and workers. The challenges faced by mothers become even greater when they have children with special needs who require more attention than typical children. This systematic review aims to explore the psychological well-being of working mothers who have children with special needs, a group facing dual pressures from professional responsibilities and caregiving demands. Based on the analysis of 10 selected peer reviewed articles (2015-2025), the findings indicate that psychological well-being is shaped by various factors, including social support, work flexibility, self-acceptance, and healthy coping strategies. Additionally, disparities in access to essential services such as counselling, inclusive daycare, and digital information pose significant challenges, particularly for mothers with lower education and digital literacy levels. While dual roles may increase stress and emotional fatigue, psychological well-being remains achievable through a combination of internal and external protective factors. Therefore, multidimensional interventions encompassing psychological, social, and policy reforms are crucial to enhance sustainably the quality of life for working mothers with special needs children.